Almost Quasi $τ^\star(σ_1,σ_2)$-continuous and Weakly Quasi $τ^\star(σ_1,σ_2)$-continuous Functions (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces two classes of continuous functions defined between an ideal topological space and a bitopological space, called almost quasi $τ^\star(σ_1,σ_2)$-continuous functions and weakly quasi $τ^\star(σ_1,σ_2)$-continuous functions. Furthermore, several characterizationsand some properties concerning almost quasi $τ^\star(σ_1,σ_2)$-continuous functions and weakly quasi $τ^\star(σ_1,σ_2)$-continuous functions are investigated. Moreover, the relationships between almost quasi $τ^\star(σ_1,σ_2)$-continuity and weak quasi $τ^\star(σ_1,σ_2)$-continuity are considered.
Keywords: almost quasi $τ^\star(σ_1,σ_2)$-continuous function; weakly quasi $τ^\star(σ_1,σ_2)$-continuous function